A REVIEW ON GREEN PRACTICES IN HOTEL INDUSTRY - Norazlina Rahmat; Muhammad Aiman Aisy Mohd Daud; Norzaidah Ngali; Muhammad Khairul Nizam Abdullah (International Journal of Accounting, Finance and Business, 2022)
Green hotel practices are efforts or changes to hotel operations that give hotels with advantages and benefits if embraced. The goal of this study is to identify studies on green hotel practices. A review approach is applied, and 38 out of 219 studies meet the search criteria. From that number,18 of those studies focusses on hotel green practices motivators. Based on the analysis of the studies, four factors motivate hotel organizations to apply green practices: competition, cost savings, growth, and the environment. International and domestic theoretical contributions from 2010 to 2022 are used in this study. The review discusses the benefits and drawbacks of green hotel policies. The findings may help the hotel industry promote more sustainable and environment practices. Finally, this study will be a helpful resource for companies looking to learn about environmentally friendly hotel management while also attempting to implement green marketing strategies.